Pengaruh Media Big Book Terhadap Hasil Belajar Siswa Kelas V Sd Dalam Pembelajaran Bahasa Indonesia - Nincy Apriliani; Rury Rizhardi; Hermansyah Hermansyah (Journal on Education, 2024)
Indonesian is one of the subjects that must be taught in elementary schools. This research is motivated by several problems such as during the teaching and learning process the learning media used when teaching is less attractive, then the teacher has not applied the big book media to the teaching and learning process. This study aims to determine whether there is an influence of big book media on the learning outcomes of fifth grade elementary school students in learning Indonesian. The population of this study was 32 students in class V, with a sample of 15 students in class V A. The research method uses a quantitative method of the Pre-experimental design (non-designs), namely the One Group Pretest-Posttest Design. Data collection techniques in this study using tests. The test instrument is in the form of essay questions totaling 5 questions to measure students' understanding abilities. The data analysis technique uses the independent sample t-test. Based on the research results, the average pretest score was 49.73, and the posttest score was 83.61. From testing the hypothesis obtained of 8.501 and value of 2.048. With a significant level of 0.05 this means > (8.501 > 2.048). So it can be stated that Ha is accepted, thus it can be concluded that there is an influence of big book media on student learning outcomes in learning Indonesian. Keywords: Media Big Book, Indonesian Language Learning